Developing The Competency of Human Resources Analyst Officials in The Personnel Agency and Human Resources Development - Nasruddin, Nasruddin; Hamid, Muliyadi; Djabar, Sadly Abdul (Newinera Publisher, 2024)
Human resource management (HRM) is a crucial element in organizational success, particularly in government institutions. This study focuses on the competency development of the functional position of Human Resources Apparatus Analyst (Analis SDM Aparatur) following job realignment at the Civil Service and Human Resource Development Agency (BKPSDM) in Nunukan Regency. The research examines the alignment of employee competencies with job demands and evaluates the effectiveness of existing competency development programs. The study employs a descriptive qualitative method with an inductive analysis approach. The findings reveal significant competency gaps among employees, both in technical skills and managerial abilities, which hinder their performance effectiveness. Moreover, existing training programs are deemed suboptimal in addressing the functional position's actual needs in terms of content, methods, and implementation. The study suggests the necessity of a comprehensive evaluation of training programs and the formulation of more targeted and relevant competency development strategies. These findings contribute to enhancing HRM effectiveness, supporting BKPSDM's strategic objectives, and serving as a reference for future HR policy-making.